Determining the Relationship between Tourism Marketing Strategy and Tourist Satisfaction - Ali, Aree M.; Saadon , Aveen I. (Polytechnic Journal of Humanities and Social Sciences, 2024)
Abstract— This paper aims to investigate the role of the tourism marketing strategy and its contribution to tourist satisfaction in Duhok Kurdistan Region-Iraq as the study sample. The organizations that apply the concepts of modern marketing take the tourist as the basis of their activity and existence and continuity, and the satisfaction of tourists is one of the areas that have received a huge number of research in recent years due to the importance that it has occupied in marketing philosophy.Satisfaction of tourists is one of the most important factors that guarantee future profit growth. Nowadays,many organizations have considered tourist satisfaction as an important criterion for measuring the quality of their work. The researchers try to shed light on tourist satisfaction by getting to know the concept of tourist satisfaction , and how to measure it.The research deals with a very important topic, which is the role of tourism marketing strategy in enhancing tourist satisfaction, and in light of this, the research sheds light on the nature of tourism marketing strategy objectives, marketing mix.Statistical tests of validity and reliability of the questionnaire, the validity of the main hypotheses, where it appeared that there is a relationship between tourism marketing strategy and tourist satisfaction at the overall level. From this point of view, the research recommends the necessity of activating the use of tourism marketing strategy as it was found that there is a strong influence relationship in achieving tourist satisfaction. Keywords—marketing strategy, satisfaction , tourist, tourism, target market.